Secondary fusion proteins as a mechanism of BCR:ABL1 kinase‐independent resistance in chronic myeloid leukaemia. (20th October 2022) - Barnes, Evan J.; Eide, Christopher A.; Kaempf, Andy; Bottomly, Daniel; Romine, Kyle A.; Wilmot, Beth; Saunders, Dominick; McWeeney, Shannon K.; Tognon, Cristina E.; Druker, Brian J.
Summary: Drug resistance in chronic myeloid leukaemia (CML) may occur via mutations in the causative BCR::ABL1 fusion or BCR::ABL1‐independent mechanisms. We analysed 48 patients with BCR::ABL1‐independent resistance for the presence of secondary fusion genes by RNA sequencing. We identified 10 of the most frequently detected secondary fusions in 21 patients. Validation studies, cell line models, gene expression analysis and drug screening revealed differences with respect to proliferation rate, differentiation and drug sensitivity. Notably, expression of RUNX1::MECOM led to resistance to ABL1 tyrosine kinase inhibitors in vitro. These results suggest secondary fusions contribute to BCR::ABL1‐independent resistance and may be amenable to combined therapies.